Intraosseous ganglion in the subchondral region of the lateral femoral condyle in an 11-year-old girl: a case report - Nakayama Hiroshi; Yagi Masayoshi; Yoshiya Shinichi (BMC, 2009)
Abstract We report the case of a patient with intraosseous ganglion in the lateral femoral condyle. An 11-year-old girl presented with right knee pain following a twisting injury. Plain radiographs of the knee showed a small circumscribed radiolucency with a thin sclerotic margin in the subchondral region of the lateral femoral condyle. Although the image findings and location are not typical, the lesion was tentatively diagnosed as osteochodritis dissecans. Six months after the conservative treatment with a break from vigorous sports activities, the size of the bony lesion had not decreased. Thus, we performed arthroscopy to make a definitive diagnosis. Arthroscopic examination revealed an area with dimple and surface irregularity at the lateral femoral condyle. On excision of the overlying tissue, the lesion was cystic containing brown mucous fluid. No association between the cyst and the articular structures was observed. Histologic examination of the resected cyst wall showed dense fibrous tissue with spotty areas of calcification. Base on these findings, we made a diagnosis of intraosseous ganglion. At the nine-month postoperative follow-up, the radiographic examination showed healing of the lesion. We speculate that the lesion in this case might have occurred as a result of repetitive overstress or microtrauma.